The reROOT coaching program: a pilot randomized controlled trial evaluating its impact on coaching style and athlete sports development - Lemelin, E.; Carpentier, J.; Gadoury, S.; Petit, É.; Forest, J.; Richard, J.-P.; Joussemet, M.; Mageau, G. A. (International Sport Coaching Journal, 2024)
The reROOT program teaches coaches 40 behaviors belonging to a need-supportive coaching style (including structure, involvement, and autonomy support), as defined by self-determination theory. This pilot randomized controlled trial, conducted during the COVID-19-related lockdown, evaluated the impact of this 18-hr program on coaching style (e.g., Problems in Sports Questionnaire) and on athlete motivation (Motivation Underlying Achievement Goals Questionnaire), performance (tactical, technical, physical, and psychological skills), and well-being (Satisfaction with Life Scale; Positive and Negative Affect Schedule). Twenty-three sports teams from two universities were randomized in the experimental or the wait-list control condition. Coaches in the experimental condition evaluated autonomy-supportive coaching styles more favorably than those in the control condition at the 1-year follow-up, but not 2 months after the end of the program. Athletes whose coaches participated in the program did not rate them as having a higher need-supportive coaching style, but experienced greater autonomous motivation and (potentially) performance, and under certain circumstances greater well-being and less controlled motivation 2 months after the end of the program compared with the wait-list condition. These findings suggest that the reROOT program could potentially improve readiness to rely on more autonomy-supportive skills and promote some aspects of sports development in athletes.